Peter Singer: Ethics Today - Vertzagia, Despina; Georgakopoulou, Trisevgeni; Kameris, Christos (Conatus - Journal of Philosophy, 2017)
On May 2015 the influential moral philosopher Peter Singer, professor of Applied Ethics at Princeton University, was honored by the National and Kapodistrian University of Athens with the title of Honorary Doctor of Philosophy for his contribution to philosophy, and especially for renewing the moral thought. Within his visit in Athens, he was invited by the Applied Philosophy Research Laboratory at the School of Philosophy, where he gave a lecture for students and professors. By the end of the lecture, we came across the chance of having a conversation with him about his main ethical standpoints on charity and animal abuse, as well as on other issues within the field of applied philosophy. Although he is the originator of preferential utilitarianism, which is the last strong ethical system, it seems that Peter Singer continues to review his beliefs and updates his view, without averting his gaze from the needs of current reality.